2019
DOI: 10.1007/s11425-018-9488-9
|View full text |Cite
|
Sign up to set email alerts
|

Group actions on treelike compact spaces

Abstract: We show that group actions on many treelike compact spaces are not too complicated dynamically. We first observe that an old argument of Seidler [37], implies that every action of a topological group G on a regular continuum is null and therefore also tame. As every local dendron is regular, one concludes that every action of G on a local dendron is null. We then use a more direct method to show that every continuous group action of G on a dendron is Rosenthal representable, hence also tame. Similar results ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…We obtained the following theorem in this paper, which extends the corresponding result for Z-actions in [11] and answered a question proposed by E. Glasner and M. Megrelishvili in [5]. Theorem 1.1.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…We obtained the following theorem in this paper, which extends the corresponding result for Z-actions in [11] and answered a question proposed by E. Glasner and M. Megrelishvili in [5]. Theorem 1.1.…”
Section: Introductionsupporting
confidence: 80%
“…Based on the results obtained by Marzougui and Naghmouchi in [8], Shi and Ye showed that every amenable group action on dendrites always has a minimal set consisting of 1 or 2 points (see [16]), which is also implied by the work of Malyutin and Duchesne-Monod (see [6,3]). Glasner and Megrelishvili showed the extreme proximality of minimal subsystems provided that the group actions on dendrites have no finite orbits (see [5]). For Z actions on dendrites, Naghmouchi proved that every minimal set is either finite or an adding machine (see [11]).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Seilder [18] proved that those systems have zero topological entropy. Recently Glasner and Megrelishvili [6] proved that they are even null (i.e their sequence topological entropy is zero). In [14,15] Naghmouchi showed that any ω-limit set is minimal and he showed that the absence of periodic point allows the presence for one and only one minimal set.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some people are interested in studying the alternative phenomena for group actions on curves (continua of one dimension). For example, it is implied by several authors' work that every subgroup of a dendrite homeomorphism group either has a finite orbit or contains a free nonabelian group (see [7,17,11]). One may refer to [12,16,26,27,28] for some related investigations in this direction.…”
Section: Introductionmentioning
confidence: 99%